(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
The article examines the relationship between the use of act technologies in the organization of electronic commerce and the introduction and use of digital technologies using information communication systems. During the research, a system for ensuring information security was developed in the realization of products of industrial enterprises through electronic commerce.